PENERAPAN STANDAR OPERASIONAL PROSEDUR PEMBERSIHAN KAMAR TAMU DI HOTEL PUSAKO BUKITTINGGI - Yulhaslinda, Yulhaslinda (Ensiklopedia of Journal, 2021)
The purpose of this study is to find out how the Standard Operating Procedures for cleaning guest rooms at Hotel Pusako Bukittinggi, the authors conducted research in the field of Housekeeping, especially in the room attendant section. and it can be concluded that Hotel Pusako especially the room attendant has implemented Standard Operating Procedures in cleaning guest rooms.